La tecnología social como política de fomento para las cooperativas de ahorro y crédito de los segmentos cuatro y cinco del Ecuador, análisis situacional - Iriarte, Carmen (2021)
This work, is a qualitative research, which carried out the exploration of application the social technology process like a development policy for four and five segments (classified by their assets level by Superintendence) Unions of Ecuador. The study used the Grounded Theory method that collected the experiences of 4 Unions general managers of these segments, the data collection was done with semi-structured interviews and questionnaires, the data analysis was qualitative in the search for a conceptual ordering, for which was used the constant comparative method of Corbin and Strauss; during the research, the theoretical interests of the participants were identified in five categories that allow the implementation of social technology (TS) as a mechanism of financial inclusion (IF) of the Unions of the lowest segments classification by their level of assets as representatives of Popular and Solidarity Finance (FPS) of Ecuador, using Information and Telecommunications Technologies (ICTs). Also, it was identified that the little or no regulation of the State through public policies contributes to inequality in the acquisition and placement of financial resources, regardless of the fact that, according to the perception of those consulted, these Unions, contributed more for development of their influence territories where operated, despite the limitations in resources to comply with the reports to the Entities and Control State Agencies, the competence of their peers from higher segments that have better and greater resources, including technological ones, that allow them to provide more efficient and diverse financial services, being Financial Inclusion, the central category that unites the others ones, the findings found as a result of this investigation were proposed TS like a inclusion financial promotion policy for the four and five segments Unions of Ecuador.